Meeting Room Booking System with WhatsApp Notification Feature Using Extreme Programming Methods in RS Muhammadiyah Lamongan - Firdonsyah, Arizona; Putri, Nafisyah Alyana (Politeknik Ganesha Medan, 2025)
Meeting room management in hospitals plays an important role in supporting operational efficiency and coordination between departments. At RS Muhammadiyah Lamongan, common issues such as overlapping schedules, delays in booking information, and lack of transparency in the scheduling process are still frequently encountered. This study aims to develop a web-based meeting room booking system using the Extreme Programming (XP) method, integrated with a WhatsApp notification feature. The system is designed to improve transparency, minimize scheduling conflicts, and enhance communication between administrators and users. Requirements gathering was conducted through interviews with the hospital's secretariat, and the system was developed using the Laravel Framework and WhatsApp API. The system testing was carried out using Blackbox Testing and User Acceptance Testing (UAT) with a Likert scale. The test results showed that the system achieved a perfect score of 100 out of 100 points, indicating that all core features functioned as expected without significant technical issues. This system is expected to serve as an effective solution to support a more efficient, real-time, and structured meeting room scheduling process at RS Muhammadiyah Lamongan.